Persepsi Siswa terhadap Integrasi Teknologi AI TalkPal dalam Pembelajaran Bahasa Arab: Indonesia - Azanulhaq, Azanulhaq; Sakaroni , Rubiyatna (Pamulang university, 2024)
The application of Artificial Intelligence in Arabic language subjects at Madrasah Aliyah is one of the alternatives to overcome various obstacles faced during the learning process. The purpose of this study is to analyse students' perceptions of AI TalkPal technology in the Arabic language learning process. The research method used is descriptive qualitative. The research sample is 11th grade students who have completed the a'mal yaumiyat learning material taken through purposive sampling technique . Data collection techniques were carried out through questionnaires (surveys) and direct interviews with students. The data obtained were then analysed descriptively. The results showed that: 1) 82% of students stated that the use of AI TalkPal can facilitate the Arabic learning process; 2) 68% of students stated that the use of AI TalkPal positively contributes to the improvement of students' Arabic speaking skills; 3) 57% of students stated that AI TalkPal can increase their interaction and involvement in the learning process; 4) 82% of students stated that AI TalkPal has a connection with the learning material; and 5) most students feel that the application of AI is very helpful and very easy to use in the learning process, but there are some obstacles in using AI TalkPal, such as inadequate mobile phone memory and poor internet signal. The use of Artificial Intelligence TalkPal in Arabic language learning can be an alternative to increase the interest and motivation to learn Arabic language of 11th grade IPA students.